2001
DOI: 10.2172/784549
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the First H-mode Discharges in NSTX

Abstract: We report observations of the first low-to-high (L-H) confinement mode transitions in the National Spherical Torus Experiment (NSTX). The H-mode energy confinement time increased over reference L-mode discharges transiently by 100-300%, as high as 1 50ms. This confinement time is ~ 1.8-2.3 times higher than predicted by a multimachine ELM-free H-mode scaling. This achievement extends the H-mode window of fusion devices down to a record low aspect ratio (R/a) ~ 1.3, challenging both confinement and L-H power th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The applied loop voltage from the solenoid is also reduced to zero during the B v ramp to maintain an approximately constant plasma current. Energy confinement times exceeding 100 ms have also been reported in NSTX H-mode plasmas [14].…”
Section: Characterizationmentioning
confidence: 85%
See 1 more Smart Citation
“…The applied loop voltage from the solenoid is also reduced to zero during the B v ramp to maintain an approximately constant plasma current. Energy confinement times exceeding 100 ms have also been reported in NSTX H-mode plasmas [14].…”
Section: Characterizationmentioning
confidence: 85%
“…DIII-D. On DIII-D it is found that P th is typically a factor ∼2 higher in a DND configuration than in SND (with the ion ∇B-drift direction towards the x-point) [12], an exception to this being at high triangularity (δ ∼ 0.8) where the lowest power threshold is observed in a DND configuration [13]. The comparable NSTX ST device at PPPL also reports similarly high H-mode threshold powers [14]. No obvious scaling of P th with e.g.…”
Section: H-mode Accessmentioning
confidence: 90%